Experience in organizing the cadets’ practical training by means of the discipline “Foreign language” - Olga V. Igumnova (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
Nowadays practice-oriented learning in higher education is fixed as a legal norm in Russian legal system. The legislator emphasizes the importance of developing students practical skills while they are at the higher school. Primarily it deals with specialized subjects of educational programs. Nevertheless, general studies, which include a foreign language, should also cover specialists/bachelors practical training.